Efisiensi Pemasaran Tandan Buah Segar (TBS) Perkebunan Kelapa Sawit Swadaya - Crysiani Crysiani; Eva Dolorosa; Marisi Aritonang (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research evaluates Fresh Fruit Bunches (FFB) marketing efficiency in Desa Sungai Ilai Kecamatan Beduai Kabupaten Sanggau. The writer used purposive sampling to collect data and determine the research samples, with 50 participants in 2023. The data analysis employed a combination of primary and secondary data and descriptive analysis and then focused on marketing margins, farmer shares, and profitability indexes. The research findings indicate three patterns of oil palm-independent smallholder FFB marketing channels in Sungai Ilai Village. All three marketing channels for oil palm FFB in Desa Sungai Ilai are considered efficient. It shows that Channel I has approximately 90.29% of the farmer's share and a marketing margin of about 9.71% (FS > MM). Channel II shows a farmer’s share of around 85.78% and a marketing margin of about 14.22%, while Channel III has a farmer’s share of about 81.26% and a marketing margin of around 18.64%. The profitability index for Channel I is 4.25, Channel II has a profitability index of 3.12, and Channel III has a profitability index of 2.74. These results affirm that all marketing channels show profitability index values >1, indicating success in achieving positive profits.